2013
DOI: 10.1111/imj.12109
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcomes of discharges against medical advice among hospitalised patients

Abstract: Patients who self-discharged against medical advice carry a significant risk of readmission and mortality. Patients with characteristics of 'at risk of DAMA' should have greater attention paid to their care before and especially after any premature discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
93
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(106 citation statements)
references
References 16 publications
10
93
3
Order By: Relevance
“…12,14 Homeless patients were also overrepresented in the AMA discharge population at Highland Hospital-a finding that has not been consistently reported in prior studies, and that warrants further examination. In adjusted analyses, Spanish speakers had a lower rate of AMA discharge, and there were no racial variations.…”
Section: Discussionmentioning
confidence: 68%
“…12,14 Homeless patients were also overrepresented in the AMA discharge population at Highland Hospital-a finding that has not been consistently reported in prior studies, and that warrants further examination. In adjusted analyses, Spanish speakers had a lower rate of AMA discharge, and there were no racial variations.…”
Section: Discussionmentioning
confidence: 68%
“…Discharges AMA might lead to adverse outcomes, readmissions to the hospital, and disproportionate use of healthcare resources for patients because of inadequate initial treatment of a medical condition [1,6,17,21,44]. Although rates and risk factors for self-discharge have been documented in other settings, including pneumonia [36], asthma [4], and gastrohepatic disorders [22,32], there has been little published regarding orthopaedic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although the observed frequency of self-discharge episodes-particularly among hospitalizations for fractures-could be considered small, the clinical and economic burden to healthcare systems may be substantial. On the basis of available evidence, it is likely that more than 21,000 patients who left prematurely after a fracture ended up having more adverse events and readmissions, ultimately resulting in higher healthcare costs-some of which are often not reimbursed to hospitals by insurance companies [6,17,44]. Aliyu [2] calculated the readmission cost resulting from a self-discharge at 56% higher than expected from the original hospitalization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,44 Several retrospective studies have identified patients with substance use disorders as having a high risk of discharge against medical advice, which is associated with increases in hospital readmissions and health care costs, as well as in the risk of death, highlighting the importance of prevention. [45][46][47][48] Qualitative research and one systematic review found that opioid withdrawal, inadequate pain management, younger age, daily heroin injection and unstable employment were factors contributing to discharges against medical advice among patients with substance use disorders. 29,49,50 Available evidence suggests that opioid agonist therapy, when paired with referral to outpatient addiction services, may reduce discharge against medical advice and increase engagement in postdischarge addiction treatment.…”
Section: Is There Benefit To Inpatient Initiation Of Opioid Agonist Tmentioning
confidence: 99%